3D Mapping of Winter Lightning in Japan with an Array of Discone Antennas. Issue 11 (3rd July 2022) - Wang, Daohong; Wu, Ting; Huang, Haitao; Yang, Junchen; Yamamoto, Kazuo
Abstract : We have developed a 3D lightning mapping system with an array of Discone Antennas working in the medium frequency‐high frequency (MF‐HF) bands. This system is called discone antenna lightning mapping array (DALMA) and has been deployed in Hokuriku area of Japan for the 3D mapping of winter lightning. Radio waves in the MF‐HF bands are rarely used for lightning 3D mapping due to large noises in these frequency bands. However, we have demonstrated in this paper that by using a wideband antenna, 3D mapping in the MF‐HF bands can also produce satisfactory results. We have analyzed two lightning flashes with complicated features observed in the last winter. In the first flash, we have successfully mapped an upward leader triggered by a negative cloud‐to‐ground (CG) lightning from a tall tower. In the second flash, we have successfully mapped a fast downward leader preceding an intense return stroke. Finally, we have also discussed the advantages of DALMA compared with other 3D mapping systems in LF or very high frequency (VHF) bands. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.